STUDI KUALITATIF: IMPLEMENTASI TEKNIK ARSIR UNTUK MENINGKATKAN KETERAMPILAN MENGGAMBAR SISWA KELAS ATAS SD NEGERI CICURUG MELALUI OBSERVASI DAN WAWANCARA - Risma Fitriani Lestari; Utomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability of upper elementary school students to apply shading techniques in producing gradient and volume effects in drawings, despite visual arts being an essential component of the Merdeka Curriculum. The study aims to describe the shading technique learning process in upper grades at SD Negeri Cicurug, identify supporting and inhibiting factors, and analyze its impact on students' drawing skills. It also refers to prior studies showing that shading techniques can enhance student creativity and artwork quality, though implementation challenges persist at the elementary level. The research employs a qualitative approach with a case study design. Subjects include 30 students from grades V–VI, the art teacher, and the school principal. Data collection techniques consist of participant observation, semi-structured interviews, and documentation over three months (September–November 2026). Data analysis follows Sugiyono's (2019) interactive model, encompassing data reduction, data display, and conclusion drawing/verification through triangulation. Data validity is ensured via member checking and peer debriefing. Findings reveal that shading technique implementation proceeds through demonstration, guided practice, and artwork evaluation stages, supported by student enthusiasm and the teacher's facilitative role. Inhibiting factors include limited concentration among some students and time constraints in lessons. Overall, shading technique instruction positively impacts the quality of students' drawing skills. This study recommends systematic integration of shading techniques into elementary visual arts instruction.